Dietary fiber modulates gut microbiome and metabolome in a host sex-specific manner in a murine model of aging - Kadyan, Saurabh; Park, Gwoncheol; Wang, Bo; Nagpal, Ravinder (Frontiers in Molecular Biosciences, 2023)
Emerging evidence reveals the fundamental role of the gut microbiome in human health. Among various factors regulating our gut microbiome, diet is one of the most indispensable and prominent one. Inulin is one of the most widely-studied dietary fiber for its beneficial prebiotic effects by positively modulating the gut microbiome and microbial metabolites. Recent research underscores sexual dimorphism and sex-specific disparities in microbiome and also diet-microbiome interactions. However, whether and how the prebiotic effects of dietary fiber differ among sexes remain underexplored. To this end, we herein examine sex-specific differences in the prebiotic effects of inulin on gut microbiome and metabolome in a humanized murine model of aging i.e., aged mice carrying human fecal microbiota. The findings demonstrate that inulin exerts prebiotic effects, but in a sex-dependent manner. Overall, inulin increases the proportion of Bacteroides, Blautia, and glycine, while decreasing Eggerthella, Lactococcus, Streptococcus, trimethylamine, 3-hydroxyisobutyrate, leucine and methionine in both sexes. However, we note sex-specific effects of inulin including suppression of f_Enteroccaceae:_, Odoribacter, bile acids, malonate, thymine, valine, acetoin, and ethanol while promotion of Dubosiella, pyruvate, and glycine in males. Whereas, suppression of Faecalibaculum, Lachnoclostridium, Schaedlerella, phenylalanine and enhancement of Parasutterella, Phocaeicola, f_Lachnospiraceae;_, Barnesiella, Butyricimonas, glycine, propionate, acetate and glutamate are observed in females. Altogether, the study reveals that prebiotic mechanisms of dietary fiber vary in a sex-dependent manner, underscoring the importance of including both sexes in preclinical/clinical studies to comprehend the mechanisms and functional aspects of dietary interventions for effective extrapolation and translation in precision nutrition milieus.